2019
DOI: 10.1101/584862
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GABA-Glutamate supramammillary neurons control theta and gamma oscillations in the dentate gyrus during paradoxical (REM) sleep

Abstract: Several studies suggest that neurons from the lateral region of the SuM (SuML) innervating the dorsal dentate gyrus (DG) display a dual GABAergic and glutamatergic transmission and are specifically activated during paradoxical (REM) sleep (PS). The objective of the present study is to fully characterize the anatomical, neurochemical and electrophysiological properties of the SuML-DG projection neurons and to determine how they control DG oscillations and neuronal activation during PS and other vigilance states… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…The segregated localization of neurotransmitter vesicles in the same terminals suggests differential co-transmission of glutamate and GABA at the SuM-DG synapses (Dugué et al, 2005;Somogyi, 2006;Vaaga et al, 2014). Consistent with this observation, SuM terminals in the DG simultaneously release both glutamate and GABA to GCs and GABAergic INs (Billwiller et al, 2020;Hashimotodani et al, 2018;Pedersen et al, 2017). Of note, the ratio of the glutamate-and GABA-mediated components recorded in INs varied from 0.34 to 7.7 (Hashimotodani et al, 2018).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…The segregated localization of neurotransmitter vesicles in the same terminals suggests differential co-transmission of glutamate and GABA at the SuM-DG synapses (Dugué et al, 2005;Somogyi, 2006;Vaaga et al, 2014). Consistent with this observation, SuM terminals in the DG simultaneously release both glutamate and GABA to GCs and GABAergic INs (Billwiller et al, 2020;Hashimotodani et al, 2018;Pedersen et al, 2017). Of note, the ratio of the glutamate-and GABA-mediated components recorded in INs varied from 0.34 to 7.7 (Hashimotodani et al, 2018).…”
Section: Introductionsupporting
confidence: 58%
“…Single plane coronal sections with bead expression were imaged using a Research High-Class Stereo Microscope System (SZX16, Olympus, Tokyo, Japan). For colocalization analysis of ChR2-eYFP expressing boutons with VGluT2 and VGAT, boutons along ChR2-eYFP expressing axons were identified in zstack images and examined for colocalization and were counted using cell counter plugin in Fiji (a distribution of ImageJ software, NIH, USA, 1.53c) (Billwiller et al, 2020).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Sections from SZ and control cases were processed for simultaneous detection of target mRNAs (CHRFAM7A, CRH, VIP) in combination with calretinin immunohistochemistry as previously described (14, 15). Paraffin embedded sections were first deparaffinized and treated with 3% H2O2 for 10 minutes, rinsed in 0.01M phosphate-buffered saline (PBS, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it was recently shown that PV+ interneurons in the cortex are more active during REM sleep, especially the subset which was active during previous waking periods 29 . These results suggest that theta oscillations within the HPC and the RSC may arise from a similar mechanism dependent on the MS, although many other regions may participate, as for instance the supramammillary nucleus 30 , the mammillary bodies 21 , or the claustrum, whose projections activate the dentate gyrus in the HPC and the RSC during REM sleep 31 . The anterior thalamic nuclei (ATN) are also strong candidates to participate in this network since they are bidirectionally connected with both the HPC and the RSC, show similar theta oscillations, and have been related to the processing of mnemonic spatial information 32 .…”
Section: Discussionmentioning
confidence: 93%